Diagnóstico da produção leiteira da agricultura familiar no Semiárido Mineiro - Isabela Rocha Menezes (2012)
The objective was to characterize 30 family dairy farms located in Juramento and Montes Claros, Northern Minas Gerais, as well as to analyze the quality of milk produced in relation to subclinical mastitis rates and the correlation with the somatic cell count (SCC); the interference of adequate milking handling on subclinical mastitis rates and the influence of the two distinct seasons (rainy and dry) on the proximate composition of the milk produced; to determine the factors related to milking handling and milk storage that offered relative risk to the quality of milk and to verify the contamination by mesophilic, psychrotrophic, coliform microorganisms at 45°C and Enterococcus spp. A diagnosis of the properties was carried out through semi-structured questionnaires and in loco observation in the beginning of the research. To determine subclinical mastitis rates, California Mastitis Test (CMT) was used; to evaluate the microbiological quality, the proximate and microbiological composition and hygiene of milking utensils, the specific methodology for each was carried out as described by Alpha (2001); in order to determine the risk factors related to handling we used the questionnaire answers, the subclinical mastitis rates and the milk quality results. It was possible to determine the risk factors denominated Odds ratio through statistics. All the statistic procedure was done via Statistical Analysis System. Sampling from CMT and milk was carried out in four steps, two of them in the dry season, during the months of June and October 2011, and two in the rainy season, in December 2010 and March 2011. CMT was carried out monthly in six properties, three located in Juramento and three in Montes Claros, during the 12 months of study in order to analyze the impact that technical assistance would have on subclinical mastitis rates. There were also courses and lectures for the producers with the purpose of helping the improvement of milk quality. It was concluded that the main characteristics of production in Northern Minas Gerais are: deficient general and hygiene handling and mixed herds that are less apt for milk production when compared to more specialized herds; the average producer is a low-income family farmer who depends on milk production to complement their revenue. Regarding agro ecological practices, it can be concluded that theywere rarely used in the properties surveyed. The rates of subclinical mastitis and SSC were influenced by the season. A higher frequency of positive tits and samples with non-standard SSC levels were observed in the rainy season. The proximate composition of milk was within the values established by law. However, there was variation between rainy and dry season in protein amount, defatted dry extract and SCC, which could have been influenced by the difference of availability and quality of forages in the two seasons as well as by the animal handling. There was positive correlation between the CMT values and SCC from the mixed herds under study. SCC had a positive correlation with protein, lactose and nonfat dry extract levels and a negative one with fat and total solids. A relative risk for total bacterial count wasnt observed regarding refrigeration and storage of milk in the properties. Inadequate milking handling practices, including improper hygiene of the tits, pre-dipping and post-dipping, offered relative risk regarding SCC levels and subclinical mastitis in herds. Despite other inadequate practices such as hygiene of the surroundings not being evaluated in relation to the relative risk, ahigh frequency of inadequacies that can interfere in the quality of milk and mammary gland health was observed. The milk presented microbiological contamination related to microorganisms that compromised the hygiene and sanitary quality of the product. There is an evident shortcoming regarding the hygiene practices adopted on the milking equipment, what leads to high contamination by aerobic mesophilic, as well as the need for the adoption of good agricultural practices. That demands higher investment in training and technical assistance on those properties so that the required microbiological quality for milk safety is reached.